Perancangan Sistem Informasi Akademik Berbasis Website Pada SMK Bina Medika Jakarta - Rahman, Taufik; Pramastya, Ananda Bagus; Nurdin, Hafis; Sumarna, Sumarna (JSAI (Journal Scientific and Applied Informatics), 2019)
A technology creation starts from the world of education, then the world of education should implement a technology-oriented information system, but in SMK Bina Medika every school academic system procedure is done manually, student data processing, absenteeism, student data search related to academics still must be open the archive sheets in the student information value section, there is no integrated data storage media because student data storage, teacher data, grade data, class data and class schedules that are done now are still using an offline application without you a database, so the problem in SMK Bina Medika, thus slowing down performance in presenting information quickly and precisely. This research aims to design a web-based academic information system. The research method used in this study is the System Development Life Cycle (SDLC) method. The design system in making academic websites uses some software namely Sublime Taxt, Xamp which is a combination of Apache Web Server, PHP, MySQL. Designing an academic information system to facilitate students, teachers and the Bina Medika Vocational High School (SMK) which was previously not available, student data, teacher data and the school is still separate so as to find out full information for quite a long time, with its website-based information system online is expected to make it easier for students, teachers and the Bina Medika Vocational High School (SMK), so that it can be more effective and efficient.